The Stereotype of American Bikers as reflected in Poison’s “Ride the Wind” and Twisted Sister’s “Ride to Live, Live to Ride” - Arido Laksono (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2019)
Bikers are often considered as brutal, unlawful and unoccupied group of people disrupting the order of society. In some cases, they belong to certain gangs committing serious crime. Yet, there are also bikers riding their motorcycles in order to experience ultimate freedom; the freedom of chasing the wind and living outdoor close to nature. The idea of American Dream puts a solid basis on the two phenomena previously mentioned. The short article reveals the stereotype of American bikers by analyzing the lyrics of Ride the Wind and Ride to live, Live to Ride. The argumentative analysis is developed and elaborated through several elements of the lyrics, sociological point of view and historical perspectives. Hence, a comprehensive discussion can be developed and acquired.                                            Keywords: Stereotype, Bikers, American Dream, Gangs, Freedom